2012
DOI: 10.1371/journal.pone.0052136
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box O1 Is Present in Quiescent Pituitary Cells during Development and Is Increased in the Absence of p27Kip1

Abstract: Congenital pituitary hormone deficiencies have been reported in approximately one in 4,000 live births, however studies reporting mutations in some widely studied transcription factors account for only a fraction of congenital hormone deficiencies in humans. Anterior pituitary hormones are required for development and function of several glands including gonads, adrenals, and thyroid. In order to identify additional factors that contribute to human congenital hormone deficiencies, we are investigating the fork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Nonetheless, it has been suggested that p27 and RB pathways mediate different modules and control cell cycle at different phases [28,29]. Combining the previous findings that CDKN1B is mediated by FOXO1 [17], we suggest that G6PC could regulate cell cycle regulation via FOXO1 pathway in OvCa, a speculation of great interest and warrants further investigation (Fig. 5e).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nonetheless, it has been suggested that p27 and RB pathways mediate different modules and control cell cycle at different phases [28,29]. Combining the previous findings that CDKN1B is mediated by FOXO1 [17], we suggest that G6PC could regulate cell cycle regulation via FOXO1 pathway in OvCa, a speculation of great interest and warrants further investigation (Fig. 5e).…”
Section: Discussionsupporting
confidence: 76%
“…2c). Of note, its interrelation with FOXO1 provided a possible bridge between G6PC and CDKN1B, as mediation of CDKN1B by FOXO1 has been previously established [17]. When interactions between G6PC1 and CDKN1B were studied, we noticed a substantially sophisticated network between the two genes, indicating lack of direct interactions between the mRNAs (Fig.…”
Section: G6pc Expression Was Increased In Ovca With Decreased Cdkn1b mentioning
confidence: 53%
“…FOXO1 is expressed in many tissues including pancreas, liver, brain, adipose, and ovary 103, 126 . FOXO1 is present in quiescent cells of the developing pituitary, consistent with a role in suppressing cell cycle progression 127 . The cell specificity of FOXO1 expression in the pituitary is not clear.…”
Section: Emerging Roles For Additional Transcription Factor Families:mentioning
confidence: 90%
“…For this study, we determined whether FOXO1 was also present in gonadotropes in dispersed primary pituitary cells in culture using mice heterozygous for GFP tagged FOXO1 ( FOXO1 tag/WT ) (57). We also evaluated somatotropes for FOXO1 expression as a previous report had found FOXO1 predominately in GH expressing cells (62). Under culture conditions, FOXO1-GFP expression co-localized with gonadotropes and a subset of somatotropes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our studies, a previous report by Majumdar et al . using a different FOXO1 antibody (Cell Signaling Technology, 2880) demonstrated that less than 10% of gonadotropes expressed FOXO1 and that FOXO1 was predominately expressed in somatotropes (62). Interestingly, under culture conditions, we observed FOXO1-GFP expression in a small subset of cells producing low levels of GH, whereas cells producing high levels of GH did not appear to express FOXO1.…”
Section: Discussionmentioning
confidence: 99%